If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 = 14 + 6x Solving 3 = 14 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 3 + -6x = 14 + 6x + -6x Combine like terms: 6x + -6x = 0 3 + -6x = 14 + 0 3 + -6x = 14 Add '-3' to each side of the equation. 3 + -3 + -6x = 14 + -3 Combine like terms: 3 + -3 = 0 0 + -6x = 14 + -3 -6x = 14 + -3 Combine like terms: 14 + -3 = 11 -6x = 11 Divide each side by '-6'. x = -1.833333333 Simplifying x = -1.833333333
| 5x-6(3)=4 | | -24=5x-x | | 5v=24-3v | | (X+5)=(2x+3) | | D+27=64 | | 7X+7=103-5x | | 133/-19 | | -6(n-4)=2-5n | | 7(3x-3)-5(3x+4)= | | 3x+wx=20 | | 4x-27+2x+7=180 | | 7-x=-2x+16 | | 21x+7-14x=-2+7x | | 3x+3(3x+4)=156 | | 37=25-2/3x | | 8x+7=8x-x | | 10-6n=2-n | | 5x+78=34-3x | | 5/9×45-32 | | 5.5x+348.25=1000 | | 2.50r=90 | | (5x+x)-(2.2x+8)= | | 6z+z=6z-2 | | 2(x+6)+7(3x-4)= | | 5(8-9m)-4=-9 | | 3.4*c-1.7=6.8 | | 3k-2+4k=-23 | | 33=3x-9 | | 5x+78=48+3x | | X+-2=10 | | x+3(-2)=1 | | 5x-3/x-1=3/2 |